Development of a HS-SPME/GC–MS method for the analysis of volatile organic compounds from fabrics for forensic reconstruction applications. (September 2018) - Gherghel, Simona; Morgan, Ruth M.; Arrebola-Liébanas, Javier; Romero-González, Roberto; Blackman, Chris S.; Garrido-Frenich, Antonia; Parkin, Ivan P.
Highlights: A sensitive SPME method suitable for trace analysis of VOCs from garments is shown. The method was validated for both natural and synthetic fibres. The method was applied to the analysis of traces of commercial perfumes from garments. The method was compared with referenced methodology proving high sensitivity. The method has been designed to be suitable for forensic investigations of assault cases. Abstract: An analytical method for the determination of trace amounts of volatile organic compounds (VOCs) relevant to the cosmetics industry was optimised, validated and employed for the analysis of commercial perfumes. The method used a combination of headspace solid phase microextraction (HS-SPME) and gas chromatography–mass spectrometry (GC–MS). In addition to fibre type, three different HS-SPME extraction conditions were investigated simultaneously, namely incubation time, extraction time and extraction temperature, using a central composite design in order to determine the optimal conditions for the extraction of VOCs of interest. The main figures of merit of the proposed method (calibration range, limits of detection and quantification, trueness and precision) were evaluated for six different VOCs in both natural and synthetic fibres in order to validate it and verify its capability for the proposed application. The validated method was applied for the analysis of traces of commercial perfumes from fabrics, and the VOCs of interest were successfully quantified. This simple, highly sensitive, and robust method has the potential to represent a powerful approach for forensic reconstructions where perfumes have transferred between individuals, such as during assaults and sexual assaults.